2011
DOI: 10.1253/circj.cj-10-0492
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Masked Hypertension and the Mask Effect' in Patients With Well-Controlled Office Blood Pressure

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp he assessment of out-of-office blood pressure (BP), using either ambulatory or home BP monitoring, has enabled detection of masked hypertension (MH) and the "white-coat" hypertension (WCH) phenomena. Studies have shown that MH carries a similar cardiovascular risk to uncontrolled hypertension (UH). 1 Both home BP self-measurement (HBP) and ambulatory BP monitoring (ABPM) have been shown to be better correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…[14][15][16] Only a Korean study defined masked hypertension using home BP measurement but it investigated treated hypertensive patients. [17][18][19] The majority of the previous studies did not find any significant differences in MS between the BP groups 14,16-20 but only one study investigated all four BP subgroups. That study performed ambulatory BP measurement on 328 untreated, non- proportion of the syndrome was higher in masked (29%) and sustained hypertension (30%) than in normotension (12%) or white-coat hypertension (17%).…”
Section: Insulin Resistancementioning
confidence: 95%
See 2 more Smart Citations
“…[14][15][16] Only a Korean study defined masked hypertension using home BP measurement but it investigated treated hypertensive patients. [17][18][19] The majority of the previous studies did not find any significant differences in MS between the BP groups 14,16-20 but only one study investigated all four BP subgroups. That study performed ambulatory BP measurement on 328 untreated, non- proportion of the syndrome was higher in masked (29%) and sustained hypertension (30%) than in normotension (12%) or white-coat hypertension (17%).…”
Section: Insulin Resistancementioning
confidence: 95%
“…[14][15][16][17][18][19][20] Although the prevalence of MS varies widely depending on the definition used, only three studies reported criteria for the syndrome. [14][15][16] Only a Korean study defined masked hypertension using home BP measurement but it investigated treated hypertensive patients.…”
Section: Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The difference of blood pressure between the 2 groups did not become small during the study period, even though all antihypertensive drugs were available through the study period, suggesting that it is not easy to control hypertension without CCB and ARB in diabetic patients, although only they are not enough to control hypertension. Several studies had reported that self-measurement of HBP was useful for detection of insufficient control of blood pressure 17 and it had better prognostic accuracy in terms of both cardiovascular morbidity and mortality than the office measurement. 12,18 HBP measurements have also been shown to predict the damage of target organ by hypertension better than office measurements.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the present study include patients with white-coat hypertension or masked hypertension. 30 Although we could not use more precise diagnostic tools, we think that the prevalence of overestimated hypertension was not so large as to affect the study results. Fifth, although a Korean prospective study showed that short sleep duration could be a risk factor for incident hypertension in postmenopausal women, we could not adjust for sleep duration.…”
Section: 711mentioning
confidence: 91%